Fish prey of the sympatric Galápagos fur seals and sea lions: seasonal variation and niche separation - Dellinger, Thomas (1999)
Analysis of fish otoliths in scats and vomits of Galápagos fur seals (Arctocephalus galapagoensis) and Galápagos sea lions (Zalophus californianus wollebaeki) was used to determine the numerical composition of the diets for the post-El Niño year 1983, the cold seasons in 1984 and 1985, and the warm season in 1986. Between 84 and 99% of all otoliths in fur seal scats were from myctophids and bathylagids. The fur seals’ diet included 26 species. Only 3 species contributed more than 1% of otoliths. No seasonal differences in diet were found. Sea lion samples contained a mean of 14 otoliths. Sardines (Sardinops sagax) contributed 75–85% of otoliths. Sea lions preyed on 24 species, but only 3 surpassed 1% abundance. Seasonality was not reflected in the sea lions’ diet. After the 1982–1983 El Niño, the diets of both species deviated from those in all other years of the study. Food-niche overlap between the two sympatric species was almost non-existent. This is hard to understand, based on our knowledge of the diving capabilities of the two species, but reflects the fact that Galápagos fur seals are nighttime foragers and sea lions are daytime foragers.